SPIA operational model and workplan (2023 – 2030) - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2023)
At the 17th System Council (SC) meeting, SC members endorsed the Standing Panel on Impact Assessment (SPIA) working with SIMEC to bring a recommendation back about addressing SPIA’s capacity needs to enable SPIA to fulfill its mandate. Following two meetings with SIMEC, on February 7 and March 2, 2023, this document sets out a proposal for a new operational model and workplan & budget (2023 – 2030) for SPIA, a proposal to allow a flexible funding mechanism, as well as updated Terms of Reference, to respond to new asks from System Council members to SPIA and to ensure adequate and appropriately configured capacity to enable SPIA to fulfill its mandate.